Opisthorchis viverrini infection causes liver and biliary cirrhosis in gerbils - Wonkchalee, Orasa; Boonmars, Thidarut; Kaewkes, Sasithron; Chamgramol, Yaovaluk; Pairojkul, Chawalit; Wu, Zhiliang; Juasook, Amornrat; Sudsarn, Pakkayanee; Boonjaraspinyo, Sirintip (Parasitology research (1987), 2011)
Opisthorchis viverrini infection causes many hepatobiliary diseases, including cholangiocarcinoma. Hence, the study of O. viverrini infection in humans is subject to ethical limitations, so an animal model, the Syrian hamster, is often used. O. viverrini can develop into the adult stage not only in Syrian hamsters but also in other animals, including gerbils, but until now, there has been no report on pathology and susceptibility in gerbils. The present study revealed the pathology of O. viverrini infection in gerbils through gross appearance, histopathology, and worm recovery at various time points. Gerbils were infected with 50 O. viverrini metacercariae and then sacrificed at the time of observation. The gross appearance of the liver showed micronodules at the liver surface, suggesting liver and biliary cirrhosis. Light microscopic observation was correlated to the gross appearance with cholecystitis, fatty liver changes, fibrous septa, and generalized cirrhosis. The range of worm burden fluctuated from 1 to 25 worms with large body size, which was correlated with pathology. These novel findings indicate that O. viverrini infection can cause liver and biliary cirrhosis in gerbils, depending on the worm burden, worm size, and habitat.